Comparison of queuing performances measures of Multi-Server counter services using DSW Algorithm method and L-R method / Khairul Niezam Abdul Aziz, Nurul Aina Syamila Mohammad Izahar and Nurul Syahira Ariffin - Abdul Aziz, Khairul Niezam; Mohammad Izahar, Nurul Aina Syamila; Ariffin, Nurul Syahira (2023)
Queues happen when the assets are restricted. Hence, queuing theory helps in the plan of adjusted frameworks that could serve clients rapidly and productively yet not expensive to ever be feasible. Moreover, the queueing issue is critical in the design of a queueing system because it involves one or more decisions such as the number of servers at a service facility and the effectiveness of the servers. When the cost coefficient and the arrival or service pattern are known precisely, the queueing choice issue may be addressed. Hence, the objectives are to measure the queuing performances of multi-server counter services using the DSW Algorithm method and L-R method and to compare which methods are suitable for the queuing performances of multi-server counters.